Presentation ready improve your sales presentation outcomes & avoid the twelve most common mistakes - Sjodin, Terri L. (McGraw Hill, 2024)
Presentation Ready is divided into three sections: building your case, leveraging creativity, and honing your delivery. Each chapter explores a specific presentation mistake-why it happens, why it's damaging, and includes practical tips on how to correct it. You may laugh or cringe at some of these confessions, stories, and observations, but they are all true. The solutions will ultimately help you course-correct to save yourself time, increase your earning potential, reduce stress, and gain greater confidence for future presentations.